National and cultural syncretism in teaching russian communication to foreign students of Asian and Pacific region - A V Gussakovskiy (Russian Language Studies, 2013)
The article is devoted to an actual problem of studying «a conceptual picture of the world model» of the students from Asian and Pacific region. Studying behavior stereotypes of this or that ethnocultural community allows to provide a purposeful training in Russian communication, based on the models of « psychological behaviour technics» of representatives of other ethnic cultures.